TINJAUAN GAYA VOKAL IBU SAINI PADA LAGU SAYUR GAMBANG KROMONG "AKANG HAJI" - Imam Firmansyah; Faisal Ibrahim; Irgi Maulana Alfahrezy (Narada : Jurnal Desain dan Seni, 2021)
Gambang Kromong singers who can sing Lagu Sayur Gambang Kromong nowadays are very hard to find. Most singers in the Gambang Kromong are dangdut singers who singing the Gambang Kromong song. This caused the number of Gambang Kromong Singers to decrease in number. One that still exists is Mrs. Saini, a singer of the Sinar Baru group from Gunung Sindur, Bogor. He has a distinctive singing style especially when singing lagu sayur. He can sing some lagu sayur that are quite rare, one of which is the song "Akang Haji". The song is quite rare, even the gambang Kromong groups in Jakarta have never played it again. This song is still often found in Udik (Bogor) and Wetan (Tangerang and surrounding areas). This study describes the vocal style of Ibu Saini in the Sayur Gambang Kromong song using audio-visual recording methods, and interviews. In terms of several elements, the vocal style is posture, breathing techniques, articulation, and resonance.